Bibliometric study on Ergonomics and Sustainability - Garcia Filho, Joao Francisco Alfonso; Sugahara, Cibele Roberta; Branchi, Bruna Angela (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Reflections on ergonomics in the context of the sustainability of organizations are an important strategy for the improvement of safe working environments. In the literature, the discussion that encompasses the relationship between ergonomics and business sustainability is a topic little explored. The objective of the present research is to map and explore the scientific production in the field of ergonomics and sustainability in the period from 2010 to 2020, in order to show the temporal evolution of research and the existing articulation between the themes. The research method is exploratory. To carry out the research, the bibliometric technique was chosen. To this end, articles were searched in the SciELO and Scopus databases, and theses and dissertations in the Digital Library of Theses and Dissertations (BDTD) of CAPES on the theme of ergonomics and sustainability. The bibliometric research allows to identify limits, contributions and potentialities that highlight the need for the production of research and new knowledge that associate the theme of ergonomics with sustainability. The development of an ergonomics program associated with the principles of sustainability seems to be a way to manage occupational risks with preventive measures in occupational safety and health.